Identification of single stranded RNA fragments recognised by TLR7/8 in Dengue and other mosquito-borne Flaviviral genomes: A bioinformatics approach - Muhammad Bashir Bello; Dawoud Usman (The Microbe)
Toll-like receptors (TLRs), particularly TLR7 and TLR8, are crucial components of the innate immune system that detect viral single-stranded RNA (ssRNA). However, excessive TLR activation can result in a hyperinflammatory response or “cytokine storm,” contributing to severe disease outcomes. In this study, we performed a genome-wide bioinformatic analysis to quantify and compare the abundance of known TLR7 and TLR8 ssRNA-binding motifs across five clinically important mosquito-borne flaviviruses: Dengue virus (DENV), Yellow fever virus (YFV), Zika virus (ZIKV), Japanese encephalitis virus (JEV), and West Nile virus (WNV). Our results show that DENV possesses the highest density of strong TLR7-binding motifs (e.g., UUU, UUC and their repeats), as well as key TLR8-stimulating sequences such as UUGU, UUAU, and the potent (UG)₃ motif. In contrast, WNV exhibited the lowest abundance of these immunostimulatory motifs. These differences may contribute to virus-specific variation in innate immune activation and disease severity. By highlighting distinct patterns of innate immune recognition among flaviviruses, our findings provide novel insights into flaviviral pathogenesis and may inform the design of RNA-based vaccines or antiviral therapeutics aimed at modulating TLR-mediated immune responses.